2016
DOI: 10.3758/s13414-016-1161-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal discrimination of one’s own reaction times in dual-task performance: Context effects and methodological constraints

Abstract: In this study we used the method of constant stimuli to investigate introspective reaction times in the psychological refractory period (PRP) paradigm under different temporal contexts. Previous introspective PRP studies have mostly used visual analogue scales to assess introspective reaction times and found that participants were largely unaware of the typical dual-task costs that arise in this paradigm (PRP effect). This apparent limitation of introspection has been taken as evidence for a serial processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
(69 reference statements)
4
18
0
Order By: Relevance
“…3 -experiments with a modality order AV (left column, Experiments 1A-C) seem to produce introspective blind spots, whereas experiments with a modality order VA (right column, Experiments 2A-C) seem to produce more accurate introspective reports. The results of Experiments 1A-C are consistent with the results of previously published introspective PRP studies that used a modality order AV (Corallo et al, 2008;Marti et al, 2010; Experiment 1 of Bratzke & Bryce, 2016; Experiment 2a of Bryce & Bratzke, 2017, Experiment 1 of Klein, 2015). In addition, which task was manipulated and exactly how this was done does not seem to affect introspection in this context.…”
Section: Interim Discussionsupporting
confidence: 88%
“…3 -experiments with a modality order AV (left column, Experiments 1A-C) seem to produce introspective blind spots, whereas experiments with a modality order VA (right column, Experiments 2A-C) seem to produce more accurate introspective reports. The results of Experiments 1A-C are consistent with the results of previously published introspective PRP studies that used a modality order AV (Corallo et al, 2008;Marti et al, 2010; Experiment 1 of Bratzke & Bryce, 2016; Experiment 2a of Bryce & Bratzke, 2017, Experiment 1 of Klein, 2015). In addition, which task was manipulated and exactly how this was done does not seem to affect introspection in this context.…”
Section: Interim Discussionsupporting
confidence: 88%
“…Previous conceptualization of IRTs in dual tasks in light of the unified attentional bottleneck model imply that IRTs reflect relatively veridical time estimates of the consciously accessible internal processing times (Corallo et al, 2008;Marti et al, 2010). Others have proposed that introspective RTs in dual-task situations reflect retrospective inferences based on a variety of cues (Bratzke & Bryce, 2016Bratzke et al, 2014;; see also Klein & Stolz, 2018). In line with the latter assumption, one could argue that in the present study, participants inferred their IRTs from, for example, their experience of the between-trial sequence of R1-R2 compatibility or of the sequence of required and performed responses (e.g., 50% of compatible-compatible and incompatible-incompatible sequences include full response repetitions).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that introspection about dual-task costs is severely limited, since participants are usually not aware of the PRP effect (Bratzke & Bryce, 2016;Bratzke, Bryce, & Seifried-Dübon, 2014;Corallo, Sackur, Dehaene, & Sigman, 2008;Marti, Sackur, Sigman, Dehaene, 2010; for a diverging pattern regarding task switch costs, see Bratzke & Bryce, 2019). To assess people's introspection, most of these studies used the method of quantified introspection (Corallo et al, 2008), in which participants provide estimates of their RTs (introspective reaction times, IRTs) after each trial.…”
Section: Introspection About Backward Crosstalk In Dual-task Performancementioning
confidence: 99%
“…According to the body of research on time expectancy, humans seem to represent time intervals not in an absolute but in a relative manner (Bausenhart, Bratzke, & Ulrich, 2016 ; Bratzke & Bryce, 2016 ; Los, Kruijne, & Meeter, 2017 ). Time expectancies are used to prepare for an upcoming task.…”
Section: Discussionmentioning
confidence: 99%